Efforts of the Aqidah Akhlak Teacher in Enhancing Students' Spiritual Intelligence through Religious Culture at MTS Jabal Rahmah Palakka, Soppeng Regency - Adrian (Universitas Muhammadiyah Palu, 2026)
One strategic effort to address this need is through the role of Akidah Akhlak teachers in internalizing religious values by cultivating a school-wide religious culture. This study aims to describe and analyze the efforts of Akidah Akhlak teachers in improving students' spiritual intelligence through religious culture at MTs Jabal Rahmah Palakka, Soppeng Regency. The research employs a qualitative approach using descriptive methods. Data were collected through in-depth interviews, direct observations, and documentation. The informants in this study consisted of the principal, Akidah Akhlak teachers, vice principal, and students from grades VII, VIII, and IX. The results show that Akidah Akhlak teachers play a central role in developing students' spiritual intelligence through well-structured and systematic religious activities such as congregational prayers, Qur'anic recitation (tadarus), group remembrance (dzikir), short religious sermons (kultum), and Islamic boarding programs (pesantren).). The religious culture established at the school is not merely symbolic, but has become a routine practice that shapes students' daily attitudes and behaviors. Values such as honesty, responsibility, discipline, and social awareness have gradually become integrated into students' character. Nevertheless, challenges remain, including lack of discipline and negative external influences. In conclusion, the efforts of Akidah Akhlak teachers through religious cultural approaches have proven to be effective in holistically and sustainably enhancing students' spiritual intelligence.